Analysis of Student Learning Outcomes on Polynomial Topic in Grade XI During the Teaching Assistance Program - Syahzaqi, Idrus; Gunawan, Syifa (Indonesian Journal Publisher, 2025)
This study aims to analyze students’ learning outcomes on the polynomial topic during the Teaching Assistance Program conducted in Grade XI. As polynomials represent a foundational concept in upper secondary mathematics, understanding students’ performance provides valuable insights into the effectiveness of instructional practices. This descriptive quantitative research analyzed daily assessment scores from 33 students using statistical measures including minimum, maximum, mean, median, mode, range, and standard deviation. The findings show a moderate performance with an average score of 67.7, a median of 70, and a standard deviation of 7.7. A total of 54.5% of students achieved the minimum mastery criterion, while 45.5% did not, indicating a substantial variation in conceptual understanding. The score distribution also demonstrated clustering around the 68–72 range, suggesting that many students possessed partial comprehension but struggled with deeper algebraic reasoning. These results highlight the need for differentiated instruction, scaffolded learning, and improved feedback mechanisms. The Teaching Assistance Program contributed significantly to the reflective development of teaching skills and provided authentic classroom experience for the pre-service teacher. Overall, this study emphasizes the importance of varied teaching approaches to enhance student mastery of polynomial concepts.